2022
DOI: 10.3390/vaccines10020153
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Anti-SARS-CoV-2 IgG Antibody Levels 6 Months after Complete BNT162b2 Vaccination in Healthcare Workers to Levels Observed Following the First Vaccine Dose

Abstract: Research on post-vaccination antibody dynamics has become pivotal in estimating COVID-19 vaccine efficacy. We studied anti-SARS-CoV-2 Spike RBD IgG levels in 587 healthcare workers (2038 sera) who completed BNT162b2 vaccination. Average antibody titer 3 weeks after the first dose in COVID-19-naïve participants (median 873.5 AU/mL) was 18-fold higher than the test threshold, with a significant increase 1 month (median 9927.2 AU/mL) and an exponential decrease 3 (median 2976.7 AU/mL) and 6 (median 966.0 AU/mL) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…With respect to long-term humoral immunity after vaccination, several studies among health care workers have reported that SARS-CoV-2 spike protein antibody titers and neutralizing antibodies progressively decline up to 6 months after vaccination [ 3 , 4 , 37 , 38 ]. Studies of HD patients in Germany showed that SARS-CoV-2 spike protein antibody titers peaked 1 month after the second vaccination in dialysis patients and declined to approximately 50% of peak values 3–4 months later [ 5 , 23 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to long-term humoral immunity after vaccination, several studies among health care workers have reported that SARS-CoV-2 spike protein antibody titers and neutralizing antibodies progressively decline up to 6 months after vaccination [ 3 , 4 , 37 , 38 ]. Studies of HD patients in Germany showed that SARS-CoV-2 spike protein antibody titers peaked 1 month after the second vaccination in dialysis patients and declined to approximately 50% of peak values 3–4 months later [ 5 , 23 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this previous report, the results of the present study demonstrated that SARS-CoV-2 spike protein antibody titers in Japanese HD patients were significantly lower (approximately one-third) than those in healthy controls 6 months after receiving the second dose of the BNT162b2 vaccine. With respect to factors associated with long-term antibody titers, studies among health care workers have shown that low antibody titers 6 months after vaccination are related to age, immunosuppressive medications, low initial doses of vaccine, and low peak values 1 month after vaccination [ 3 , 38 ]. In dialysis patients, age, use of immunosuppressive agents, low albumin levels, and low hemoglobin levels are reportedly associated with low antibody titers 6 months after vaccination [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, neutralizing assays are complex and time-consuming and anti-S IgG titers are commonly used as surrogate marker to understand efficacy and durability of vaccine administration [19][20][21]. A recent paper reported a consistent correlation between these parameters, indicating that specific antibody responses to SARS-CoV-2 are time-dependent [22]. Six months after the first cycle of vaccination with BNT162b2, the immune humoral responses waned especially in men, individuals older than 65 years and among individuals with immunosuppression [23].…”
Section: Discussionmentioning
confidence: 99%
“…So this indicator may have prognostic value in developing vaccination recommendations for some groups of individuals. However, further research is needed to elucidate the relationship between specific IgG and infection protection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%